An Analysis Of Products And Services Delivered By Agri-Input Dealers Trained Under DAESI - Tanya Saklani,; B. Shilpa,; G Naveen Kumar,; Sugandha Munshi, (Journal of Agricultural Extension Management, 2026)
Agricultural input dealers, also known as agri-input dealers, play a critical role in the agricultural ecosystem as vital intermediaries between agricultural technology providers and farmers. This research paper aims to explore the product and services being offered by the DAESI trained agri-input dealers. By exploring the products and services offered by them to the farmers, this paper aims to understand the current trend of products and services to provide a comprehensive analysis of these offerings. Ex-post facto research design was used for the present study. Based on Census method, all the 20 states where DAESI is being implemented were selected. Selection of respondents was done using Simple Random Sampling method. The data was collected physically during July-December 2022. Only fully filled responses were selected for analysis of data which brought rendered the final sample size to be 166.The results revealed that majority (94.58%) of the respondents were male, the average age of the respondents was 37.26 years, about(42.78%) possessed a Graduation degree, more than half of the respondents (56.63%) had business as their prime occupation, maximum number of the respondents (75.90%) sold fertilizers, 69.88 per cent of them dealt in pesticides/insecticides while 65.66 per cent of the respondents offered seeds as agri-inputs to the farmers. About 65.06 per cent of the respondents have established Extension Corners in their shops after going through DAESI diploma course. The services they provided consultancy/advisory services (42.78%), market-support (32.53%), soil-testing (27.11%) and water-testing (12.05%).